Influence of antihypertensive drugs in the subtype diagnosis of primary aldosteronism by adrenal venous sampling. Issue 7 (July 2019) - Nagasawa, Motonori; Yamamoto, Koichi; Rakugi, Hiromi; Takeda, Masao; Akasaka, Hiroshi; Umakoshi, Hironobu; Tsuiki, Mika; Takeda, Yoshiyu; Kurihara, Isao; Itoh, Hiroshi; Ichijo, Takamasa; Katabami, Takuyuki; et al.
Abstract : Objectives: Because of the influence on the renin–angiotensin–aldosterone system, it is recommended to avoid, if possible, the use of angiotensin-converting-enzyme inhibitors, angiotensin II type 1 receptor blockers, diuretics, β-blockers, and mineralocorticoid receptor antagonists during the diagnostic period of primary aldosteronism. A laterality index more than 4 in adrenocorticotropic hormone (ACTH)-stimulated adrenal venous sampling (ACTH-AVS) is a widely used classification of the unilateral subtype that can benefit from adrenalectomy. Here, we revealed clinical features of patients taking drugs that could affect the primary aldosteronism diagnosis (DAPD) and investigated whether the classification with laterality index more than 4 in ACTH-AVS is applicable to these patients. Patients and methods: Using a large database of primary aldosteronism patients in Japan, we analyzed 2122 patients with successful ACTH-AVS. Results: Patients who received any DAPD ( n  = 209) showed higher prevalence of comorbidity burdens and took more antihypertensive drugs compared with patients without DAPD. In patients taking DAPD, those with laterality index more than 4 had a higher prevalence of hypokalemia, a higher aldosterone-to-renin ratio and a higher prevalence of adrenal mass than those with laterality index of 4 or less. Adrenalectomy was performed in 76% patients with laterality index more than 4 and 20% with laterality index of 4 or less. Patients who underwent adrenalectomy showed biochemical cure in 89% with laterality index more than 4 and 50% with laterality index of 4 or less ( P  = 0.001). Multivariate regression analysis showed that laterality index more than 4 was an independent predictor of a biochemical cure. Biochemical cure rate in patients with laterality index more than 4 was consistently high, irrespective of the potential effect of individual DAPD on laterality index. Conclusion: Our findings suggest that in primary aldosteronism patients to whom DAPD were administrated due to severe clinical features, laterality index more than 4 in ACTH-AVS could accurately predict a biochemical cure after adrenalectomy.